2021
DOI: 10.1097/rct.0000000000001175
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of the Fat Distribution of Body, Skeletal Muscle Mass and Muscle Quality on Acute Pancreatitis Severity: A Retrospective Cross-Sectional Study

Abstract: ObjectiveWe aim to investigate a possible relationship between acute pancreatitis (AP) and body fat and muscle parameters in computed tomography (CT).MethodsComputed tomography images of 107 patients with AP were scored in terms of AP severity using the modified CT severity index. Muscle mass, muscle mass index, visceral and subcutaneous adipose tissue area, multifidus muscle/fat attenuation ratio, total psoas index (TPI) and Hounsfield units average calculation (HUAC) values were performed.ResultsTotal psoas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
(78 reference statements)
0
5
0
Order By: Relevance
“… 34 Evaluation of the relationship between AP and CT-determined muscle parameters showed that the TPI was significantly higher in patients with MAP than with MSAP and SAP, as well as being substantially lower in patients with severe pancreatic necrosis than in those without necrosis. 35 To date, however, no studies have evaluated the relationship between PMA and AP. To our knowledge, the current study is the first to investigate the predictive value of PMA in patients with AP.…”
Section: Discussionmentioning
confidence: 99%
“… 34 Evaluation of the relationship between AP and CT-determined muscle parameters showed that the TPI was significantly higher in patients with MAP than with MSAP and SAP, as well as being substantially lower in patients with severe pancreatic necrosis than in those without necrosis. 35 To date, however, no studies have evaluated the relationship between PMA and AP. To our knowledge, the current study is the first to investigate the predictive value of PMA in patients with AP.…”
Section: Discussionmentioning
confidence: 99%
“…PE is important for assessing the severity and prognosis of AP and is the main symptom of extrapancreatic involvement of AP [ 29 ]. Although PE can also be detected radiologically early, most of them occur earlier than the date of pancreatic injury, and the incidence of PE increases with increasing CTSI score [ 30 ]. This revealed that PE can be recommended as a reference technical index for the diagnosis of severe pancreatitis, especially if PE is found within 24 hours after onset, and the mortality rate will be significantly improved.…”
Section: Discussionmentioning
confidence: 99%
“…21 In the very early stage of severe patients, there is more fluid sequestration, and consequently, edema gives false-high values by affecting measurements. 26 However, limited significant data have been reported for diuretics, enteral nutrition, comorbidities and time since the onset of HTGP. Although myosteatosis is associated with different pathological conditions, its pathogenesis remains uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…The latter is much more common in patients during the course of AP 21 . In the very early stage of severe patients, there is more fluid sequestration, and consequently, edema gives false‐high values by affecting measurements 26 . However, limited significant data have been reported for diuretics, enteral nutrition, comorbidities and time since the onset of HTGP.…”
Section: Discussionmentioning
confidence: 99%